Self-Triggered Apoptosis Enzyme Prodrug Therapy (STAEPT): Enhancing Targeted Therapies via Recurrent Bystander Killing Effect by Exploiting Caspase-Cleavable Linker - Chung, Seung Woo; Choi, Jeong Uk; Cho, Young Seok; Kim, Ha Rin; Won, Tae Hyung; Dimitrion, Peter; Jeon, Ok-Cheol; Kim, Seong Who; Kim, In-San; Kim, Sang Yoon; Byun, Youngro (WILEY, 2018)
Tumor heterogeneity is associated with the therapeutic failures of targeted therapies. To overcome such heterogeneity, a novel targeted therapy is proposed that could kill tumor populations with diverse phenotypes by delivering nonselective cytotoxins to target-positive cells as well as to the surrounding tumor cells via a recurrent bystander killing effect. A representative prodrug is prepared that targets integrin alpha v beta 3 and releases cytotoxins upon entering cells or by caspase-3. This allows the prodrug to kill integrin alpha v beta 3-positive cells and upregulate caspase-3, which in turn, activates the prodrug to release a cytotoxin that could subsequently diffuse into and kill the neighboring tumor cells. Apoptotic cells further upregulate and release caspase-3, which activate more prodrugs leading to another round of adjacent cell death and caspase-3 release. Thus, the bystander killing effect could occur repeatedly, leading to augmented and widespread anticancer activity. This strategy provides an avenue that could advance the current targeted therapy.
Keywords: TUMOR HETEROGENEITY; DRUG-DELIVERY; IN-VIVO; DOXORUBICIN; THERAPEUTICS; EVOLUTION; ESTERASE; RGD